Legal Responsibility of the Expedition Company for Consumer Losses Due to Loss of Goods in the Goods Delivery Service it Provides - Gandhi Pharmacista (SEAN Institute, 2024)
This research aims to analyze the legal responsibility attached to expedition companies related to loss of goods in the delivery process and its impact on consumers. The phenomenon of lost goods during delivery often raises questions regarding the legal obligations of expedition companies in compensating for losses experienced by consumers. This research uses normative and empirical legal research methods by exploring data through interviews with related parties and analysis of relevant legal documents. The research results show that cargo and expedition companies have strong responsibilities in the distribution of goods based on legal grounds, such as Article 91 of the Commercial Code and the Consumer Protection Law. Responsibility involves aspects such as security, quality assurance, and correct information to consumers. Law Number 22 of 2009 emphasizes the responsibility of public transportation companies for consumer losses during the delivery process. The dispute resolution process can be carried out peacefully through conciliation, mediation or arbitration, before involving the Consumer Dispute Resolution Agency or court. If a violation occurs, consumers can file a civil lawsuit in accordance with Articles 1244-1245 of the Civil Code to enforce their rights. In addition, expedition companies that provide insurance can be considered a form of legal protection in accordance with the insurance principles regulated by Law Number 2 of 1992.